THE EFFECT OF PRODUCT VARIATION, SERVICE QUALITY AND FACILITIES ON CONSUMER PURCHASING DECISIONS OF MIE AYAM HOTPLATE IN SURAKARTA - Alisa Karim Sekar Ayu Sejati; Supawi Pawenang; Ratna Damayanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine whether product variations, service quality, and facilities have an effect on purchasing decisions at Mie Ayam Hotplate in Surakarta and analyze which variables are the most dominant in influencing purchasing decisions. In this study, the population refers to consumers of Mie Ayam Hotplate with a sample of 100 respondents. Activity method used quantitative. The analysis carried out included multiple linier regression and hypothesisi testing. Based on the results of data analysis, it can show that product variations have a positive and significant effect on purchasing decisions, this is evidenced in statistical analysis where the regression coefficient of product variation (b1) is 0,226 and t count > t table is 3,241 > 1,985 and sig t 0,000 < 0,05. Service quality has a positive and significant effect on decisions, this is evidenced in statistical analysis that the regression coefficient value of purchase decisions (b2) is 0,376 and t count > t table is 2,257 > 1,985 and sig 0,015 < 0,05. Facilities have a positive and significant effect on purchasing decisions, this is evidenced in statistical analysis where the facility regression coefficient (b3) is 0,404 and t caount > t table is 2,671 > 1985 and sig 0,000 < 0,05.